Rightless Migration in India: A Study of Inefficiency and Sufferings Sprouting in the Agricultural Fields of Bihar - Mohan, Shivani; Kumar, Manoranjan (Journal of Ecohumanism, 2024)
The state of Bihar, an agrarian economy, is currently representing a paradoxical situation in India as the development narrative of north and south Bihar displays a unique history of economic advancement. During the Covid-19 pandemic, spurt in migration and even reverse migration created a severe livelihood crisis for the unemployed people in Bihar. United Nations’ Sustainable Development Goals of economic growth, social cohesion, and environmental sustainability can be successful in improving the lives of labourers if the socio-economic protection and workers’ rights are given due importance. The present study aims at explicating the reasons for unemployment, migration and poor economic conditions of labour in Bihar, a state in eastern part of India. Secondary data available from NSSO, Census of India and Economic survey of Bihar have been analysed for this research. The study is based on the qualitative and quantitative analysis and descriptive methods to understand the various socio-economic facets of migration. Absence of uniform labour standards in the unorganised sector related to migrant labourers is the major issue which needs to be immediately and adequately addressed by the Government of India and the state government of Bihar.